Exploring And Development Of Pathways To Supply Chain Agility And Firm Performance: Role Of Competitive Capabilities In CPEC - Haseeb Akhtar , Muhammad Maroof Ajmal , Zia-Ur-Rehman , Dr. Safdar Hussain (Migration Letters, 2024)
The agile supply chain is the competitive approach of manufacturing firms for developing and achieving sustainable market competitive position, developing better products and customer reach to achieve the objective of enhanced market & financial performance. In any country, Infrastructure has considered as mandatory factor to ensure the smooth operation of logistics activities. Therefore, as countries focus on development of infrastructure in any region, firms also needs to focus on their supply chains to harvest the benefits of infrastructure for achieving the efficiency & effectiveness. The study aimed to examine the role of infrastructure framework in relation with firm’s performance, through appropriately matched logistics activities for competitive capabilities through procreating role of SC agility. The systematic[1] review of previous studies has provided base for development of theoretical framework of the proposed relationship. The data has collected through a large-scale questionnaire from individuals of 100 CPEC associated firms, selected across the Pak-China Economic Corridor. The hypothesis testing deductive approach has used to validate the proposed framework by using SEM technique through deployment of smart PLS. The empirical evidence proposes that infrastructure framework takes no significant direct impact on performance of manufacturing firms however; relationship of infrastructure framework and firm’s performance has mediated through SC agility. The study result also shown that logistic activities for competitive capabilities mediate the relationship between supply chain agility and infrastructure framework. Further the results validate that serial mediation exits between relationships of infrastructure framework, logistics activities for competitive capabilities, supply chain agility and organizational performance. The study provide an overview and empirically indicate a contribution to theory for understanding the enablers of agile supply chains and pathways to understand how infrastructure framework can breed supply chain agility by synchronizing logistic capabilities for competitive advantages.